Comparison of plasma and cerebrospinal fluid proteomes identifies gene products guiding adult neurogenesis and neural differentiation in birds - Voukali, Eleni; Veetil, Nithya Kuttiyarthu; Němec, Pavel; Stopka, Pavel; Vinkler, Michal (Scientific reports, 2021)
Cerebrospinal fluid (CSF) proteins regulate neurogenesis, brain homeostasis and participate in signalling during neuroinflammation. Even though birds represent valuable models for constitutive adult neurogenesis, current proteomic studies of the avian CSF are limited to chicken embryos. Here we use liquid chromatography-tandem mass spectrometry (nLC-MS/MS) to explore the proteomic composition of CSF and plasma in adult chickens (Gallus gallus) and evolutionarily derived parrots: budgerigar (Melopsittacus undulatus) and cockatiel (Nymphicus hollandicus). Because cockatiel lacks a complete genome information, we compared the cross-species protein identifications using the reference proteomes of three model avian species: chicken, budgerigar and zebra finch (Taeniopygia guttata) and found the highest identification rates when mapping against the phylogenetically closest species, the budgerigar. In total, we identified 483, 641 and 458 unique proteins consistently represented in the CSF and plasma of all chicken, budgerigar and cockatiel conspecifics, respectively. Comparative pathways analyses of CSF and blood plasma then indicated clusters of proteins involved in neurogenesis, neural development and neural differentiation overrepresented in CSF in each species. This study provides the first insight into the proteomics of adult avian CSF and plasma and brings novel evidence supporting the adult neurogenesis in birds.
Keywords: proteom; neurogeneze; ptáci; Animals; Birds; Proteome; zvířata; Neurogenesis